Β-Lactam resistance development affects binding of penicillin-binding proteins (PBPs) of Clostridium perfringens to the fluorescent penicillin, BOCILLIN FL. (April 2020) - Park, Miseon; Sutherland, John B.; Rafii, Fatemeh
Abstract: Alteration in the binding of bacterial penicillin-binding proteins (PBPs) to β-lactams is important in the development of drug resistance. The PBPs of wild type Clostridium perfringens ATCC 13124 and three β-lactam-resistant mutants were compared for the ability to bind to a fluorescent penicillin, BOCILLIN FL. The binding of the high molecular weight protein PBP1, a transpeptidase, to BOCILLIN FL was reduced in all of the resistant strains. In contrast, the binding of BOCILLIN FL to a low molecular weight protein, PBP6, a D-alanyl-d -alanine carboxypeptidase that was more abundant in all three resistant strains, was substantially increased. A competition assay with β-lactams reduced the binding of all of the PBPs, including PBP6, to BOCILLIN FL. β-Lactams enhanced transcription of the putative gene for PBP6 in both wild type and resistant strains. This is the first report showing that mutations in a high molecular weight PBP and overexpression of a low molecular weight PBP in resistant C. perfringens strains affected their binding to β-lactams.